1994
DOI: 10.1038/nsb0294-102
|View full text |Cite|
|
Sign up to set email alerts
|

The active site of methanol dehydrogenase contains a disulphide bridge between adjacent cysteine residues

Abstract: Adjacent cysteine residues can only form disulphide bridges in a distorted structure containing a cis-peptide link. Such bridges are extremely uncommon, identified so far in the acetyl choline receptor alone where the structure of the bridge is undetermined. Here we present the first molecular description of a disulphide bridge of this type in the quinoprotein methanol dehydrogenase from Methylobacterium extorquens. We show that this structure occurs in close proximity to the pyrrolo-quinoline quinone prosthet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
85
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(87 citation statements)
references
References 21 publications
2
85
0
Order By: Relevance
“…The first conformational analysis of the oxidized Cys-Cys dipeptide suggested that the ring might lead to a turn when found in the middle of a peptide chain (20)(21)(22)(23)(24)(25). The analysis of model peptides confirmed that the formation of the vicinal disulfide bond is accompanied by the appearance of a tight ␤-type turn, and this phenomenon is also used in rational peptide design (26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The first conformational analysis of the oxidized Cys-Cys dipeptide suggested that the ring might lead to a turn when found in the middle of a peptide chain (20)(21)(22)(23)(24)(25). The analysis of model peptides confirmed that the formation of the vicinal disulfide bond is accompanied by the appearance of a tight ␤-type turn, and this phenomenon is also used in rational peptide design (26)(27)(28)(29).…”
Section: Resultsmentioning
confidence: 87%
“…It occurs in quite unrelated proteins such as the J-Atracotoxin from Hadronyche versuta (26), methanol dehydrogenase from Methylobacterium extorquens (27)(28)(29), the ethanol dehydrogenase from Pseudomonas aeruginosa (30), acetylcholine-binding protein from Lymnaea stagnalis (31), thioesterase I from Bos taurus (32), carboxypeptidase T from Thermoacinomyces vulgaris (33), and antimicrobial peptide hepcidin-25 from Homo sapiens (34) (Fig. 4 A-G).…”
Section: Resultsmentioning
confidence: 99%
“…A disulfide bond between adjacent cysteines joined by a cis-peptide bond has been rarely reported, i.e. only for methanol dehydrogenase (39) and human ribonuclease inhibitor (40). In methanol dehydrogenase from Methylobacterium extorquens, the disulfide bond formed by Cys 103 and Cys 104 lies immediately above the pyrroloquinoline quinone.…”
Section: Resultsmentioning
confidence: 99%
“…Such an atypical disulfide bridge, connecting residues that are adjacent in sequence, is rare in available protein structures. Two of these proteins are members of the alcohol dehydrogenase family, specifically methanol dehydrogenase from Methylobacterium extorquens (48,49) and ethanol dehydrogenase from Pseudomonas aeruginosa (50). The atypical disulfide bridge may stabilize the non-planar semiquinone form of the enzyme's prosthetic group pyrroloquinoline quinone (49).…”
Section: Zinc Is a Competitive Active Site Inhibitor That Binds To Thementioning
confidence: 99%